Scientific Stewardship in the Open Data and Big Data Era Roles and Responsibilities of Stewards and Other Major Product Stakeholders - Peng, Ge; Ritchey, Nancy A.; Casey, Kenneth S.; Kearns, Edward J.; Prevette, Jeffrey L.; Saunders, Drew; Jones, Philip; Maycock, Tom; Ansari, Steve (D-Lib magazine, 2016)
Introduces the stewardship roles of data steward, scientific steward, and technology steward for quality and useability management of digital environmental data products in this era of Open Data and Big Data. Defines and formalises their roles and high-level responsibilities as well as the responsibilities of other major product stakeholders, including data originators and distributors, and others within the context of shared responsibility for ensuring and improving data quality and product usability from the dataset-centric scientific data stewardship perspective. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.